Análise de risco para projetos legislativos que impactam o modelo Zona Franca de Manaus: uma proposta de análise de dados abertos - Cannavale, Victor (Universidade Federal do Tocantins, 2022)
This project has as main objective to analyze the risk of bills for the model of Manaus Free Trade Zone. This is a research with exploratory and structured analysis of data from the House of Representatives, in the period of 2010-2018, with application of logistic regression model. The goals established were: analyze the development of the western Amazon region and the Manaus Free Trade Zone model, as well as its tax incentives policy; evaluate the legislative process of the House of Representatives, through the mapping of the variables that influence the process of passing laws; verify the panorama of open government in Brazil, and finally, establish methodological criteria and data selection for the creation of the model using artificial intelligence.